2010
DOI: 10.1186/bcr2795
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer research output, 1945-2008: a bibliometric and density-equalizing analysis

Abstract: IntroductionBreast cancer is the most common form of cancer among women, with an estimated 194,280 new cases diagnosed in the United States in 2009 alone. The primary aim of this work was to provide an in-depth evaluation of research yield in breast cancer from 1945 to 2008, using large-scale data analysis, the employment of bibliometric indicators of production and quality, and density-equalizing mapping.MethodsData were retrieved from the Web of Science (WOS) Science Citation Expanded database; this was sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 19 publications
(18 reference statements)
4
50
0
Order By: Relevance
“…Nowhere have these increases been as evident as in breast cancer research; one recent analysis demonstrated an average 15% increase in output annually since 1945, and a greater than 100% increase since the millennium alone [1]. Allied to the growth in output has been the development of the internet and the emergence of a ''publish or perish'' culture wherein researchers feel increasingly pressured to generate ''publishable'' results [2].…”
Section: Introductionmentioning
confidence: 98%
“…Nowhere have these increases been as evident as in breast cancer research; one recent analysis demonstrated an average 15% increase in output annually since 1945, and a greater than 100% increase since the millennium alone [1]. Allied to the growth in output has been the development of the internet and the emergence of a ''publish or perish'' culture wherein researchers feel increasingly pressured to generate ''publishable'' results [2].…”
Section: Introductionmentioning
confidence: 98%
“…It has been used to create ''top cited articles'' in several specialties [2][3][4]. It has also been used in more novels ways to assess research output and funding [5,6], to identify research gaps within a specialty [7,8], with some grant authorities using this technique to decide on where funding should be distributed.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of scientific literature in oncology increased rapidly during the last 50 years [14]. Systematic evaluation of research output is necessary to guide individual reading, to plan research activities according to shortcomings and to quantify individual and collaborative productivity on national and international level.…”
Section: Introductionmentioning
confidence: 99%